The Influence of Infrastructure on the Non-Base Economic Sector in Batu City - Tjokorda Nirarta Samadhi; Maria Christina Endarwati; Agustina Nurul Hidayati; Alfin Juliandra (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The non-base sector, which can be considered a non-leading sector, may address issues in the non-base sector with proper management. In the future, development should not only rely on the existing base sector but also optimize the potential of the non-base sector in Batu City. The existence of infrastructure is crucial in supporting economic and social development, as good infrastructure can enhance effectiveness and efficiency for both businesses and society. Therefore, this study is expected to serve as a reference for government programs aimed at improving the non-base sector in Batu City. Data collection was conducted using observation techniques, questionnaires, and documentation, followed by analysis through Economic Sector Analysis, Priority Non-Base Sector Analysis, and Multiple Regression Analysis. Based on the analysis of the non-base economic sector, five sectors were further analyzed using the Analytical Hierarchy Process (AHP) to determine the priority non-base sector. From the four selected respondents, the priority non-base economic sector identified in Batu City is the transportation and warehousing sector. The analysis results indicate that infrastructure, including roads, electricity, and telecommunications, does not significantly impact the transportation and warehousing sector. Therefore, these infrastructures need to be improved in the future to enhance the economy through the non-base sector in Batu City.